Physico-chemical properties and organoleptic acceptability of star fruit (Averrhoa bilimbi Linn.) jam with variations of natural sweeteners - Dewi, Arda Rospita; Juwitaningtyas, Titisari (Journal of Halal Science and Research, 2024)
Belimbing wuluh (Averrhoa bilimbi Linn.) is a fruit plant from Indonesia that has a very sour taste because it contains citric acid and oxalic acid. This sour taste is why this fruit has yet to be optimally utilized. This study aimed to determine the effect of natural sweetener variations on wuluh star fruit jam's physico-chemical and organoleptic properties. This study used an experimental method in which the experiment was designed in a completely randomized design (CRD) with 4 treatments and 3 repetitions. The results of this study showed that the addition of natural sweeteners to wuluh star fruit jam had a significant effect (p < 0.05) on viscosity (9143 – 9450 mpa.s), sineresis (1.295 – 4.592 mg), vitamin C test (17.540 – 25.629 mg/100g), moisture content (23.57 – 31.19%), total sugar content (58.01 – 69.41%wb) and which had no significant effect (p>0.05) on pH (3.38 – 3.64%). Meanwhile, organoleptic testing did not significantly affect taste, color, texture, aroma, and spreadability parameters.   Keywords: Belimbing wuluh, Cassava sugar, Corn sugar, Honey, Jam